Linguistic and dialectal diversity in the Tareg (Tuareg) society and its relation to cultural diversity in the Hoggar region - adjailia, bouchra; ameur, bensaid (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : Algeria is the epicentre of various linguistic phenomena and embraces multilingualism and bilingualism. It has linguistic overlap; These phenomena are caused by multiculturalism and other causes. This combination of linguistic phenomena depicts Algeria ' However, the language of origin for the inhabitants of this area is Amazigh; The latter has a variety of dialects, such as Targia, Kabili,Mizabe... and others. And the targia is most areas of Algerian wastefulness have cultural and linguistic specificities, which are certified by the Tasali rock art. There are those who interpret this dialect into a language of its own that embraces multiple dialects, where the impact of this linguistic diversity is reflected in the region of Alhogar to linguistic enrichment; It is a natural linguistic phenomenon imposed by human necessity under the conscience of society's cultural diversity.